(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the key strategic decisions made by sport club management and what strategic alternatives are available to them? Purpose: The purpose is to help the management of non-profit sport clubs by identifying key strategic dilemmas and their strategic alternatives. Method: The analysis of economic, political and other social factors that influenced the sports industry was used. Then, a review of the management literature is used for an explanation of the production process specifics and identification of three key strategic dilemmas. Results: Three dilemmas identified are: a) the focus on sport results vs. the development of the local community, b) quick achievement of goals vs. reducing the level of risk, c) reduction of costs vs. organizational growth. Based on different combinations, the article presents five basic alternative orientations, namely: a) strategic focus on sports results, b) strategy of inorganic growth, c) strategy of organic growth, d) strategy of local community development, and e) strategy of increasing organizational reserves. Organization: The study offers a new classification of strategies for non-profit sports clubs. Society: The study emphasizes the importance of the relationship between sports clubs and the local community, and shows how this relationship changes according to the chosen strategy. Originality: A new classification of strategic alternatives. One of the first surveys on key business decisions of non-profit sports clubs in South-East Europe. Limitations / further research: Further research between sports clubs over a long period of time, in different environments, and in different sport branches is recommended.